Personal Prophetic Leadership, Sharia Compliance, and Islamic Corporate Governance: Sharia Banking Fraud Prevention Efforts - Mubtadi, Novendi Arkham; Adinugraha, Hendri Hermawan (LPPM Universitas Terbuka, 2022)
This study aims to discuss the chances of developing the concept of prophetic leadership, sharia compliance, and Islamic corporate governance can be linked as very important elements in preventing fraud in Islamic commercial banks. This type of research conducted in this research is qualitative research. The data collection technique used is literature study by collecting information and data with the help of various materials in the library such as documents, books, journals, notes, or by internet searching. The data analysis method using inductive and deductive thinking frameworks. The result of this study is that personal prophetic leadership (Perpec-L), sharia compliance, and Islamic corporate governance are an effort of Islamic banking to prevent fraud (corruption). This can be done by adopting the values ​​contained in Perpec-L. Then by assessing the indicators contained in sharia compliance. Furthermore, by taking the existing principles of Good Corporate Governance (GCG) that are in accordance with Islamic norms and values.